Analisis Potensi Ekonomi dan Kelayakan Usaha Budidaya Ikan Mas (Cyprinus carpio) Pada Lahan Bekas Padi Di Patoko Kecamatan Walenrang, Luwu Sulawesi Selatan - Syamsuri Syamsuri; Hasria Alang (Jurnal MeA (Media Agribisnis), 2023)
The purpose of this study is to analyze the economic potential and feasibility of goldfish farming in Patoko Village, Luwu Regency. The type of research is descriptive, while the variables of this research are the economic potential and the feasibility of goldfish farming on former paddy land. Data collection was carried out by simple random sampling through observation and interviews. The results of the study indicate that the business of cultivating carp in former rice planting fields has economic potential because it is profitable and can finance the operational needs of the business. This cultivation business is also considered feasible to be restarted based on the analysis results of OP, BCR, PP, BEP production and value, as well as the ROI value.